Heterophyllin B, a cyclopeptide from Pseudostellaria heterophylla, improves memory via immunomodulation and neurite regeneration in i.c.v.Aβ-induced mice. (August 2022) - Deng, Jiahang; Feng, Xinyue; Zhou, Longjian; He, Chuantong; Li, Huilin; Xia, Juan; Ge, Yuewei; Zhao, Yuntao; Song, Cai; Chen, Lei; Yang, Zhiyou
Graphical abstract: Highlights: Pseudostellaria heterophylla and heterophyllin B promote axonal regeneration. Heterophyllin B protect neurons from Aβ-induced apoptosis. Heterophyllin B alleviates Aβ-induced memory deficits and neuroinflammation. Network pharmacology accelerates mechanism clarification of heterophyllin B on AD. Abstract: Pseudostellaria heterophylla, has historically been used as medicine food homology plant for thousand years in China. Our previous studies had indicated that daily intake of Pseudostellaria heterophylla extract enhanced cognitive memory. Herein, heterophyllin B (HET-B), a brain permeable cyclopeptide from Pseudostellaria heterophylla was determined, and the molecular mechanism underlying its memory improvement effects was investigated. Pseudostellaria heterophylla extract as well as HET-B reversed Aβ25-35-induced axonal atrophy and neuronal apoptosis in cultured cortical neurons of mice. HET-B could enhance memory retrieval, modulate splenic T helper cell, and ameliorate neuroinflammation in i.c.v. Aβ1-42 injected Alzheimer's disease (AD) mice. To explore the mechanism of action, network pharmacology was performed to predict protein targets and pathways of HET-B against AD. Five key targets were identified related to the effect of HET-B in AD intervention, and were clarified involved in axonal regeneration. We revealed for the first time that HET-B promoted memory retrieval through axonal regeneration and anti-neuroinflammation. This study provides a basis to research on HET-B as nutritional supplements for brain healthy.